Liquid membrane tip extraction of malathion - Husnul Fatimah, Husrin (2011)
The application of liquid membrane tip extraction (LMTE) for the extraction of organophosphorus pecticide (OPP) which is malathion was investigated. The LMTE was performed in dip extraction mode. The extraction parameters that were optimized are the type of extraction solvent, time of extraction and agitation of extraction. Quantification of the malathion was carried out using High Performance Liquid Chromatography (HPLC). Optimization was carried out using water sample spiked with malathion. Under the optimum conditions which are acetonitrile as a solvent of extraction, 60 min and 60 rpm, the method showed good regression which is 0.9986 and showed acceptable reproducibility (RSD 7%), low limits of detection of 1.2 mg/L for malathion, and satisfactory relative recoveries (90%). Due to the low cost, the LMTE device was disposed after each run. The validated method was tested for the analysis of analytes in spiked tap water with good success. LMTE expected to be able to provide low cost, simple technique and rapid extraction.